The State of Food and Agriculture 2010-2011 - Food; Agriculture Organization of the United Nations (United Nations, 2011)
This edition of The State of Food and Agriculture makes the “business case” for addressing gender issues in agriculture and rural employment. The agriculture sector is underperforming in many developing countries, in part because women do not have equal access to the resources and opportunities they need to be more productive. The gender gap imposes real costs on society in terms of lost agricultural output, food security and economic growth. Promoting gender equality is not only good for women; it is also good for agricultural development.